IMPLEMENTASI ILMU SOSIO ANTROPOLOGI DALAM KEHIDUPAN BERMASYARAKAT ( STUDI ANALISIS HUBUNGAN ANTARA AGAMA, FILSAFAT DAN KEINDAHAN ) - Sujito, Ernata Hadi (Ekonomi Syariah STAI Sangatta Kutai Timur, 2020)
Beauty comes from the word beautiful which means good, scenic, beautiful, cute, and so on. Things that contain beauty are all the results of art and the universe created by God. Very wide area of ​​beauty for humans. Therefore when, where, and anyone can enjoy beauty. Beauty is synonymous with truth. Both have the same value; timeless and has an ever-increasing appeal. What does not contain truth is not beautiful. Beauty is universal. Since the 18th century, this notion of beauty has been struggling with philosophers. Beauty can be distinguished as an abstract quality and as a certain thing that is beautiful. According to the breadth of beauty, there are three definitions, namely beauty in a broad sense, in a purely aesthetic sense, and in a limited sense in relation to vision. Beauty in a broad sense contains ideas of goodness, character, laws, thoughts, opinions, and so on. Beauty in an aesthetic sense is called